2014
DOI: 10.3329/jbau.v12i1.21245
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gastrointestinal parasites of herbivores at Dhaka National Zoological Garden of Bangladesh

Abstract: A total of 52 fecal samples were collected from 21 herbivores at Dhaka zoo during January to May, 2012 to investigate the prevalence of gastrointestinal parasites of herbivores. Overall prevalence of parasitic infection was 76.9%, of which 61.5% were positive for helminths and 55.8% were positive for protozoa. The identified parasites were Balantidium coli (55.8%), Paramphistomum sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 11 publications
9
32
2
1
Order By: Relevance
“…Prevalence of Paramphistomum sp. was 44.44% in this study, which was slightly less than the report of Rehman et al (2014) where they showed 36.5% prevalence in 21 herbivore zoo species in Bangladesh. Paramphistomum generally occurs in rumen, reticulum and small intestine and cause intestinal wall erosions, haemorrhage, oedema and necrosis of ruminal papillae (Love & Hutchinson 2003).The infection of Ascaris sp.…”
Section: Discussioncontrasting
confidence: 54%
“…Prevalence of Paramphistomum sp. was 44.44% in this study, which was slightly less than the report of Rehman et al (2014) where they showed 36.5% prevalence in 21 herbivore zoo species in Bangladesh. Paramphistomum generally occurs in rumen, reticulum and small intestine and cause intestinal wall erosions, haemorrhage, oedema and necrosis of ruminal papillae (Love & Hutchinson 2003).The infection of Ascaris sp.…”
Section: Discussioncontrasting
confidence: 54%
“…Aucune espèce de trématode ou de cestode n'a été identifiée. Rahman et al (2014) au Bangladesh, Opara et al (2010) au Nigeria, et Mir et al (2016) en Inde font le même constat. Ceci est très probablement lié au fait que les trématodes et la majorité des cestodes, à l'exception de Hymenolepis nana, ont besoin d'hôtes intermédiaires, absents des enclos et cages, pour boucler leur cycle évolutif (Atanaskova et al, 2011).…”
Section: Infestation Des Primates Non Humainsunclassified
“…Several studies on ecology, biology, life history and aquaculture of O. pabda have been conducted (Breder and Rosen, 1966;Rahman, 1989;Menon, 1999;Kohinoor et al, 2009;Banik et al, 2012).…”
Section: Conservation Actionmentioning
confidence: 99%
“…This catfish was available in beels, ponds, rivers and inundated fields (Rahman, 1989) as well as streams and lakes (Menon, 1999) but now it is seriously declining in the main streams (IUCN Bangladesh, 2000).…”
Section: Abundancementioning
confidence: 99%